2022
DOI: 10.3390/cancers14133093
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiological Trends of Hepatobiliary Carcinomas in Austria 2010–2018

Abstract: Using national registries, we investigated the epidemiological trends of hepatobiliary carcinomas in Austria between 2010 and 2018 and compared them to those reported for the periods of 1990–1999 and 2000–2009. In total, 12,577 patients diagnosed with hepatocellular carcinoma (n = 7146), intrahepatic cholangiocarcinoma (n = 1858), extrahepatic cholangiocarcinoma (n = 1649), gallbladder carcinoma (n = 1365), and ampullary carcinoma (n = 559), between 2010 and 2018, were included. The median overall survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…In the group of patients that were diagnosed with HCC between 2010-2018, the overall survival improved significantly to 9.3 months (p < 0.001). [6] We took a closer look at the survival of patients without liver cirrhosis compared to those with cirrhosis. Even though not proven to be statistically significant, the median survival time of patients without cirrhosis was on average longer than those with cirrhosis.…”
Section: Survival Analysis Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the group of patients that were diagnosed with HCC between 2010-2018, the overall survival improved significantly to 9.3 months (p < 0.001). [6] We took a closer look at the survival of patients without liver cirrhosis compared to those with cirrhosis. Even though not proven to be statistically significant, the median survival time of patients without cirrhosis was on average longer than those with cirrhosis.…”
Section: Survival Analysis Discussionmentioning
confidence: 99%
“…[5] Between 2010 and 2018 a total of 7,146 individuals were diagnosed with HCC in Austria, of which 75% were male and 25% were female. [6] HCC mainly develops in the setting of underlying liver cirrhosis. [1] Hepatitis B Virus (HBV) is still the leading underlying cause of HCC globally, due to its high prevalence in Asia and Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Among women, there were comparable changes but at a higher level of significance. Studies from other countries have reported improvements in survival from ICC varying from moderate [ 24 , 25 ] to non-significant [ 19 ]. Substantial improvements have been obtained only among patients undergoing surgical treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, a study based on data from the Surveillance, Epidemiology, and End Results database found no significant change in survival from ICC between 1975 and 2016 [ 19 ], with a substantial improvement being reported only in patients undergoing surgical treatment [ 23 ]. A moderately favourable trend has been observed in some European countries during the past two decades [ 5 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is a highly prevalent malignant disease with high mortality rate, and is currently one of the top three cancers in the world in terms of mortality (Hucke et al., 2022 ). When diagnosed, only a small percentage of patients can be treated by surgical resection or liver transplantation to obtain a relatively ideal therapeutic effect (Tsai et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%